Passivation of aluminum nanopowders for use in energetic materials; Combustion, Explosion, and Shock Waves; Vol. 9, iss. 1 - Lerner M. I. Marat Izrailyevich; Glazkova E. A. Elena Alekseevna; Vorozhtsov A. B.; Rodkevich N. G.; Volkov S. A.; Иванов А. Н. Алексей Николаевич (2015, 2015)
Title screen